Sustainable development and the limits of gender policies on corporate boards in Europe: A comparative analysis between developed and emerging markets - María del Carmen Valls Martínez; Pedro Antonio Martín-Cervantes; María del Mar Miralles-Quirós (European Research on Management and Business Economics (ERMBE), 2022)
Sustainable development is a priority to the United Nations. Moreover, investment managers consider environmental, social and governance score as an important variable in portfolios selection. The fifth goal in the 2030 Agenda is gender equality. Besides, European countries have established gender quotas on corporate boards to reduce the gender gap. Empirical studies about the influence of women directors on the company's corporate social responsibility (CSR) presented mixed results, especially in developing countries. This article compares the influence of gender diversity on corporate boards on CSR performance in developed and emerging European markets. We apply a panel data methodology with fixed effects to examine the companies listed in the MSCI Europe and MSCI EM Europe indices from 2010 to 2019. The results show that gender diversity on the board of directors influences CSR performance positively, and this influence is greater in developed countries. Consequently, legislation should promote gender policies.
Keywords: M14; M 48; G3; 650; Corporate social responsibility; Gender policies; Sustainable development